Association between evergrande FC's club debt and Chinese super league's profitability from 2014 to 2019 - Liu, Zeyong; Liu, Yuqian, Agudamu; Bu, Te; Matic, Radenko; Corilic, Dusan; Casaru, Catalina; Zhang, Yang (Frontiers in Sports and Active Living, 2023)
Purpose This study examined the role of Evergrande FC's club debt on the Chinese Super League (CSL)'s profitability from 2014 to 2019. Methods We extracted the financial statements of Evergrande FC and evaluated its correlation with the profitability of CSL and Evergrande Group, which serves as a direct indicator of commercial growth. Results The association between Evergrande FC's net loss and gross debt and CSL's profitability is positive, strong (all correlation coefficients > .89), and statistically significant (all p < .05). The association between Evergrande FC's net asset value and CSL's profitability is negative, strong (correlation coefficient = −.97), and statistically significant (p < .05). Conclusion These data imply that there is a good likelihood of a causal relationship between the negative club returns generated by real estate investments and CSL's rapid commercial growth from 2014 to 2019. In essence, a dovish monetary-regulatory policy nexus during this period drove up the CSL premium. This business history from the sports industry is another illustration of how the modern coupling of economic leverage and regulatory policy could have asymmetric impacts on short-term market growth. Based on this debt-fueled business history, CSL should progress to a higher level of development in the future.